2016
DOI: 10.4111/icu.2016.57.1.50
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of KORCC (KOrean Renal Cell Carcinoma) database

Abstract: PurposeThe purpose of this article is to report establishment of the 1st Web-based database (DB) system to collect renal cell carcinoma (RCC) data in Korea.Materials and MethodsThe new Web-based DB system was established to collect basic demographic and clinicopahtological characteristics of a large cohort of patients with RCC in Korea. Data from a total of 6,849 patients were collected from 8 tertiary care hospitals that agreed to participate in organizing the Korean Renal Cell Carcinoma (KORCC) study group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Furthermore, they only analyzed patients with cRCC. As RCC is a heterogeneous and complex disease [24, 25], its results may not be directly applicable to patients with non-cRCC. In a study of 228 patients with non-mRCC, Jagdev et al [22] reported that NLR was not an independent prognostic factor for disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they only analyzed patients with cRCC. As RCC is a heterogeneous and complex disease [24, 25], its results may not be directly applicable to patients with non-cRCC. In a study of 228 patients with non-mRCC, Jagdev et al [22] reported that NLR was not an independent prognostic factor for disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…A database of 7,047 patients with RCC who were treated surgically between 1999 and 2011 at eight academic centers was reviewed. The database listed patient clinicopathologic characteristics including age at diagnosis, gender, body mass index (BMI), comorbidities (diabetes and hypertension), Eastern Cooperative Oncology Group (ECOG) performance status, surgical approach (open vs. laparoscopic), clinical tumor characteristics (tumor location, cTNM stage), tumor pathology (histologic tumor size, pTN stage, Fuhrman nuclear grade, histologic subtype, lymphovascular invasion, and surgical margin status), disease recurrence and site of recurrence (local or metastatic), and information on deaths and their causes (20). Patients with an incomplete data set (n = 1,457) and those with non-RCC pathology or pediatric RCC patients (younger than 18 years) (n = 412) were excluded; the final study group comprised 5,178 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiological studies have recently conducted sub‐analyses to better understand obesity paradox, because RCC has a heterogeneous, and complex nature . One meta‐analysis demonstrated that the effects of BMI on CSS and overall survival varied according to tumor stage .…”
Section: Discussionmentioning
confidence: 99%
“…First, it is the first study to demonstrate the age‐based prognostic value of BMI for RCC, which may improve our understanding of the obesity paradox in predicting RCC prognosis. Second, it included a large multicenter cohort of 2092 patients with nm‐cRCC, which provides clearer information regarding this condition than if we had included patients with all forms and states of RCC, because RCC has a heterogeneous, and complex nature . Third, it considered obesity‐associated factors, such as a diabetes, and hypertension, as well as the most widely accepted prognostic factors for nm‐cRCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation